The internationalisation of corruption : scale, impact and countermeasures - Fletcher, Clare (Gower, 2012)
In recent years, corruption scandals have hit the headlines all around the world, across a diverse range of institutional, organisational and cultural settings. This book embraces definitions of corruption; its scale and measurement; its causes and consequences; and counter measures.